Pendapatan Usaha Peternak Kambing: Studi Kasus di Desa Sarimulyo, Kecamatan Ngawen, Kabupaten Blora - Anisya, Ayu Putri Merry; Agustiana, Dwinita (LP3M Universitas Putra Bangsa, 2025)
This study thoroughly analyzes the income of goat farmers in Desa Sarimulyo, Ngawen Subdistrict, Blora Regency, Central Java. The research method used was Purposive Sampling to determine the research location, followed by a census method to collect data from a total of 30 goat farmers. The results of the study revealed that feed costs are the most significant component of production costs, accounting for the majority of the farmers' total expenditure. On the revenue side, the sale of poel goats (mature male goats) contributes the most to the farmers' total revenue, followed by the sale of breeding goats (mature female goats) and cempe (kids). Overall, goat farming businesses in Desa Sarimulyo show the potential to generate a positive net income, with total revenue of Rp 15,040,000 and total production costs of Rp 1,228,326, resulting in a net income of Rp 13,811,674. This study emphasizes the importance of efficient cost management, especially feed costs, to optimize the profitability of goat farming businesses. Furthermore, strategies to maximize revenue from the sale of poel and breeding goats are also an important factor in increasing farmers' income. This study provides valuable insights into the structure of costs and revenues in small-scale goat farming businesses, as well as their implications for farmers' income and economic sustainability.